Pioneer Jewish Texans - Ornish, Natalie (Texas A & M University Press, 2011)
With more than 400 photographs, extensive interviews with the descendants of pioneer Jewish Texan families, and reproductions of rare historical documents, Natalie Ornish's Pioneer Jewish Texans quickly became a classic following its original release in 1989. This new Texas A & M University Press edition presents Ornish's meticulous research and her fascinating historical vignettes for a new generation of readers and historians. She chronicles Jewish buccaneers with Jean Lafitte at Galveston; she tells of Jewish patriots who fought at the Alamo and at virtually every major enga.